The Commission the uncensored history of the 9/11 investigation - Shenon, Philip (Twelve, 2008)
New York Times reporter Philip Shenon investigates the investigation of 9/11 and tells the inside story of the most important federal commission since the Warren Commission. Shenon uncovers startling new information about the inner workings of the 9/11 commission and its relationship with the Bush White House.--From amazon.com.